(untitled) (Pashupati Pragya पशुपति प्रज्ञा, 2025)
This article explores overlaying research questions of how contextual factors and power dynamics influence stakeholders’ experiences of participation in the social audit process. It is field-based research for a single unit of analysis of a case of a community school. Field information was collected using multiple sources such as discussion and semi-structured interviews with stakeholders, available research documents, and review of empirical studies. The selection of a community school in Kathmandu was purposive because the school has a history of conducting social audit over the years. School’s participatory culture of organizing social audit regularly has been an enabler for participation of stakeholders. Formation of social audit committee and conduct of social audit report sharing program every year has created positive impact on the stakeholders. Knowledge and resource asymmetry among stakeholders played the role of barrier for some participants especially students and parents while other group of stakeholders especially teachers and those with good education and better socio-economic background were empowered to participate actively in the process. To sum up, four layers of influence created by institutional participatory culture, design process of social audit, knowledge and resource asymmetry among stakeholders have positively or negatively influenced the participation process.